Toughening of nanomultilayer and nanocomposite DLC films - Chan, Wei Chern. (2011)
Research had been carried out for the past few decades to improve material properties and produce materials with high hardness to improve reliability. In recent years, hard materials or coatings are no longer enough to satisfy the market demands for better and longer lasting materials. Hardness in the material usually comes with poor ductility or results easily into brittle fracture. Therefore, there is a need to look into improving the material in this aspect of fracture toughness of the material. Limiting the scope of improving toughness to only thin films coating, this project provides qualitative and quantitative analysis on the fracture toughness of Ti doped nanocomposite diamond-like carbon (DLC) and nanomultilayer. Ti doped DLC contains a nanocrystalline titanium carbide (nc-TiC) and a matrix formed by amorphous carbon (a-C). Preparation of the Ti doped DLC and nanomultilayer were based on the target power density. Chemical bonding structure, crystals orientation, hardness and coating adhesion will be considered in this investigation to improve the toughness of the thin films. Based on the experimental results, fracture toughness increases with the increase of Ti target power density when a higher fraction of Ti is added to the sample to form more nc-TiC. However, it is also observed that target power density have to be curbed below 300W or the fraction of sp3 bonded carbon will decrease thus reducing material hardness. Energy based method was chosen to calculate the quantitative values of toughness for each sample.